(untitled) (International Journal of Engineering and Computer Science, 2017)
-In this paper total charge of multigate MOSFET is calculated by using centroid model. Analytical modeling of total inversion charge is computed using self consistent model. The total Charge is analyzed for various value of gate to source voltage and results are discussed. The model is based on charge quantisation within the channel and it includes overshoot velocity effect